Hubungan Agama Dalam Kehidupan Masyarakat Di Bali - Kadek Widiastuti (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2020)
Humans are individuals as well as social. Humans are called social. Because every human being cannot live alone without the help of others, other people who ask permission at this time are self-confident people, given that no human being is perfect, humans are created the most perfect of God's other creations. Mutual holding and helping saving between Gods represent a noble attitude that must be instilled in social life. In social life, human beings as social beings cannot be separated from the rules that apply to the area where they are. Discussing about society related to sociology, where sociology represents the study of society. In Indonesia, almost all people have a belief or belief, religious people admit having great strength because they believe in God.